The relationship between smartphone addiction and sleep quality among University students - Naufal, Shahab (2025)
This study is to investigates the relationship between smartphone addiction and sleep quality at University Malaysia Pahang Al-Sultan Abdullah students. Smartphone use is becoming increasingly common, especially among students that raising questions about how it can affect sleep quality, which is a crucial factor in determining how well one is feeling physically, mentally, and emotionally. The study used a convenience sampling technique to gather data from 398 students involved from all faculties which is FIST, FTKKP, FTKMA, FTKA, FTTKEE, FIM and PSM by using questionnaires such as the Sleep Quality Scale (SQS) and the Smartphone Addiction Scale-Short Version (SAS-SV). The relationship between smartphone addiction and sleep quality scale was also assessed using Spearman’s Correlation analysis. The study has found that, students who had a low smartphone addiction were identified as 52.26% and those who had high smartphone addiction as 47.7%. Majority of the participants with 99.0% has poor sleep quality and 1.0% of participants having a good sleep quality. The analysis found a weak positive correlation between smartphone addiction and sleep quality. This means that when people became more addicted to smartphones, so their sleep quality became more worse. This results also indicated that there is a significant relationship between smartphone addiction and sleep quality among University students (r= 0.322, P<0.05). This study shows a connection between technology use and health outcomes while providing practical advice for improving students' academic achievement and quality of life.